Processing of porous glass ceramics from highly crystallisable industrial wastes. (24th October 2015) - Chinnam, R. K.; Bernardo, E.; Will, J.; Boccaccini, A. R.
Abstract : This study was carried out to gain understanding about the sintering behaviour of highly crystallisable industrial waste derived silicate mixtures under direct heating and rapid cooling conditions. The materials used in this study were plasma vitrified air pollution control waste and rejected pharmaceutical borosilicate glass. Powder compacts sintered under direct heating conditions were highly porous; compacts with particle size < 38 μm reached a maximum density of 2.74 g cm − 3 at 850°C, whereas compacts with particles of size < 100 and < 250 μm reached maximum densities of 2.69 and 2.72 g cm − 3 at 875 and 900°C respectively. Further increase in sintering temperature resulted in a rapid decrease in density of the glass ceramics. Image analysis results were used to link the sudden drop in density to the increase in volume of microsized pores formed in the samples during sintering. In particular, compacts made from < 38 μm particles sintered at 950°C resulted in 65 vol.-% porosity with a pore size of ∼20 μm. Such materials can be used for sound and thermal insulation purposes.